Uniqueness of nonlinear differential polynomials sharing simple and double 1-points - Indrajit Lahiri; Nintu Mandal (International Journal of Mathematics and Mathematical Sciences)
We prove two theorems on the uniqueness of nonlinear differential polynomials, one of which improves a result of Fang and Hong.